Alberti's Linguistic Innovations - Vena, Michael (Italian Literature: Roots and Branches . Essays in Honor of Thomas Goddard Bergin, 1976)
Keywords: dept.wll

Luigi Chiarelli (1880-1947): Profile of a Playwright - Vena, Michael (Connecticut Review, 1974)
Keywords: dept.wll; ⛔ No DOI found

Vertizonte - Geada, Rita (Hispanova, 1977)
Keywords: dept.wll; faculty_collection

Offprint of Italian Literature: Roots and Branches: Essays in Honor of Thomas Goddard Bergin - Bergin, Thomas Goddard; Rimanelli, Giose; Atchity, Kenneth John (Yale University Press, 1976)
Vena, Michael. Alberti's linguistic innovations.
Keywords: dept.wll; faculty_collection

La Maschera E Il Volto - Chiarelli, Luigi (Nutmeg Press, 1975)
Keywords: dept.wll; faculty_collection

Estudio Estilistico Del Quijote. - Méndez-Peñate, Sergio A. (Graficesa, 1972)
Keywords: Cervantes Saavedra, Miguel de, 1547-1616. Don Quixote; dept.wll; faculty_collection

The Importance of the Spanish Language for North Americans - Méndez-Peñate, Sergio A. (s.n., 1972)
Keywords: Spanish language; United States; dept.wll; faculty_collection

The Spanish and Spanish-American Novel - Méndez-Peñate, Sergio A. (s.n., 1972)
Keywords: History and criticism; History and criticism; Spanish American fiction; Spanish fiction; dept.wll; faculty_collection

El Humanismo De Mariano Picón-Salas; Comunicación Leida En El Iv Congreso De La Asociación Internacional De Hispanistas, Celebrado En La Universidad De Salamanca, España, 30. Viii/4. Ix, 1971. - Méndez-Peñate, Sergio A. (Graficesa, 1971)
Keywords: Picón-Salas, Mariano, 1901-1965; dept.wll; faculty_collection

Manuel González Prada Y Su Obra Poética. - Méndez-Peñate, Sergio A. (Grandes figuras literarias de Hispanoamérica, 1971)
Keywords: González Prada, Manuel, 1844-1918; dept.wll; faculty_collection

Intermediate German. - Werba, Henry (Holt, Rinehart and Winston, 1971)
Keywords: English; German language; Textbooks for foreign speakers; dept.wll; faculty_collection

Cinco Poetisas Cubanas, 1935-1969. - Aparicio Laurencio, Angel; Del Prado, Pura; Roja, Teresa Maria; Geada, Rita; Nunes, Ana Rosa (Colección Espejo de paciencia, 1970)
Keywords: 20th century; Cuban poetry; dept.wll; faculty_collection

Marcel Aymé et le Merveilleux. - Dumont, Jean-Louis (Debresse, 1970)
Keywords: Aymé, Marcel, 1902-1967; Marvelous, The, in literature; dept.wll; faculty_collection

Mascarada. - Geada, Rita (Nudo al alba ; no. 40, 1970)
Keywords: SCSU Faculty Scholar Award; award_winner; dept.wll; faculty_collection

Valle-Inclán Y La Plástica - Llorens, Eva (Insula, 1975)
Keywords: Art; Knowledge; Valle-Inclán, Ramón del, 1866-1936; dept.wll; faculty_collection; unidentified

Book Review: Fedorov, N.F. (1828-1903) - Study in Russian Eupsychian and Utopian Thought - Lukashevich, S - Wellek, ND (Alternative Futures, 1979)
Keywords: book.review; dept.wll; ⛔ No DOI found